STX17-DT facilitates axitinib resistance in renal cell carcinoma by inhibiting mitochondrial ROS accumulation and ferroptosis - Yihui Pan; Shuang Liu; Guannan Shu; Minyu Chen; Liangmin Fu; Cheng Chen; Yimeng Chen; Qianfeng Zhuang; Dong Xue; Xiaozhou He (Cell Death and Disease)
Abstract Axitinib resistance remains a serious challenge in the treatment of advanced renal cell carcinoma (RCC), and the underlying mechanisms are not fully understood. Here, we constructed an in vivo axitinib-resistant RCC model and identified the long non-coding RNA STX17-DT as a driver of therapy resistance in RCC. The expression of STX17-DT was significantly elevated in axitinib-resistant RCC cells and correlated with poorer prognosis in RCC patients. Elevated levels of STX17-DT contributed to the development of resistance to axitinib both in vitro and in vivo. Mechanistically, STX17-DT modulated the stability of IFI6 mRNA by recruiting and binding to hnRNPA1, leading to decreased accumulation of mitochondrial reactive oxygen species (ROS) and attenuated ferroptosis. Meanwhile, STX17-DT was packaged into extracellular vesicles through hnRNPA1, thus transmitting axitinib resistance to other cells. Compared with axitinib monotherapy, combined treatment of axitinib and STX17-DT-targeted in vivo siRNA demonstrated enhanced therapeutic efficacy. These findings indicate a novel molecular mechanism of axitinib resistance in RCC and suggest that STX17-DT may serve as a prognostic indicator and potential therapeutic target to overcome resistance to targeted therapy.